Detection of t(14;16)(q32;q22) and Monosomy 13 by FISH Analysis in a Patient with Multiple Myeloma Associated with Sjögren’s Syndrome: The First Case Report from India - Rupesh R. Sanap; Arundhati S. Athalye; Prochi F. Madon; Boman N. Dhabhar; Mahendra B. Sute; Amit A. Mahabale; Dhanashree J. Warang; Firuza R. Parikh (Case Reports in Genetics)
Sjögren’s syndrome (SS) is a chronic slowly progressive autoimmune disorder characterized by symptoms of oral and ocular dryness, exocrine dysfunction, and lymphocytic infiltration of exocrine glands. Multiple myeloma (MM) is a bone-marrow-based malignant neoplasm of plasma cells associated with serum/urine monoclonal paraproteins and lytic skeletal lesions. There have been very few reported cases of MM, who had SS as the first presentation. We report a case of a woman diagnosed with Sjögren’s syndrome, who was later suspected to have multiple myeloma on serum protein electrophoresis. Fluorescence in situ hybridization (FISH) was carried out to check for deletions of loci 13q14.3, ATM, p53, and IGH (14q32) rearrangements on a bone marrow aspirate. Monosomy 13 was observed in 49% of cells, and a rearrangement at the IGH locus was seen in 42% of cells. To determine the partner chromosome associated with the IGH rearrangement, further FISH tests were set up for t(4;14)(p16;q32) followed by t(14;16)(q32;q22) on fresh slides. The test was negative for t(4;14) but positive for t(14;16) in 27% of cells. This confirmed the diagnosis of MM. We report the first case from India, having an association of Sjögren’s syndrome with multiple myeloma, which showed t(14;16) and monosomy 13 by FISH analysis.